1999
DOI: 10.1118/1.598632
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the noisy component of anatomical backgrounds

Abstract: The knowledge of the relationship that links radiation dose and image quality is a prerequisite to any optimization of medical diagnostic radiology. Image quality depends, on the one hand, on the physical parameters such as contrast, resolution, and noise, and on the other hand, on characteristics of the observer that assesses the image. While the role of contrast and resolution is precisely defined and recognized, the influence of image noise is not yet fully understood. Its measurement is often based on imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 18 publications
(16 reference statements)
4
119
0
Order By: Relevance
“…However, projection images contain anatomical overlaps that limit their efficacy. 23 Thus, there may be a relative merit in using one imaging mode over the other. In a previous article, we demonstrated potential clinical advantages of using projection images; 24 however, no comparison of performance between projection images and reconstructed slices was presented.…”
Section: Discussionmentioning
confidence: 99%
“…However, projection images contain anatomical overlaps that limit their efficacy. 23 Thus, there may be a relative merit in using one imaging mode over the other. In a previous article, we demonstrated potential clinical advantages of using projection images; 24 however, no comparison of performance between projection images and reconstructed slices was presented.…”
Section: Discussionmentioning
confidence: 99%
“…17 Its strategy consists of match filtering the image by the shape of the signal profile filtered by the visual-response function. In our experiments, we considered the signal to be known and always located at the same position (signal known exactly case).…”
Section: Model Observermentioning
confidence: 99%
“…Many investigators [3][4][5][6][7][8][9][10][11][12] have shown that it is not the system (including quantum) noise that is the limiting factor in chest radiography, but rather the projected patient anatomy or "anatomical noise". It therefore follows that any images used to optimise a digital radiographic system for chest radiography must contain clinically realistic anatomical features and noise.…”
Section: Advances In Knowledgementioning
confidence: 99%